Secure Car Parking System Using VHDL (International Journal of Innovative Research in Computer Science & Technology, 2022)
The usage of automobiles is rising  nowadays days and people, resulting in more pollution,  traffic jams, and parking space difficulties, with finding a  free parking spot becoming increasingly challenging. A  Verilog HDL-based system for safe automotive parking  management is proposed in this research. This machine is  made up of three main parts. To begin, locate the vacant  slot and determine the distances. Second, book the  appointment in online mode. The entering and exit of  passwords are addressed. Safety measures number three.  Our execution time is drastically reduced when we use  FPGA. This project is about building a software that  simplifies the process of finding available parking spots  and monitoring of parked cars in a parking lot. Due to the  huge increase in availability and utilisation of parking  spaces, finding an empty spot has become significantly  more difficult. In recent years, there has been an increase  in the number of automobiles. As the number of  automobiles on the road grows, traffic congestion and  pollutants increase (noise and air pollution). An FPGA based parking system has been developed to overcome this  issue. This article uses terminology like empty parking,  Verilog HDL, traffic congestion, and vehicles.
Keywords: VHDL; Xilinx; sensor; proximity sensor